2017
DOI: 10.1177/1354856516686481
|View full text |Cite
|
Sign up to set email alerts
|

We beat the cops in GTA: Po(ludic)al activism in the age of video games

Abstract: This article explores how individuals reflect on their digital experiences of actualizing fantasies to make sense of their everyday actions, particularly in the context of video gaming. Our study takes a qualitative approach to understanding the context of materializing consumer fantasies, as initially experienced and actualized in video games, and how these fantasies are transformed into material reality, through an investigation of an illustrative case of mass street protests, the 2013 Gezi Protests in Turke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…Koenitz (2014) and Sezen and Sezen (2016) have each investigated how Turkey's protest games such as Occupy Istanbul (2013) appropriate game structures, logics, discourses, and popularity to showcase forms of civic participation within the safety of the virtual domain, but in ways that might draw players into the actual activist frontlines. Drawing on previous work by Emre et al (2014), Demirbag-Kaplan and Kaplan-Oz (2018) have suggested that a new grammar of playful resistance that is identifiable across both the Tahrir Square and Hong Kong protests is founded in a ubiquitous recognition and understanding of the game-like qualities of social and political unrest. Extending upon Demirbag-Kaplan and Kaplan-Oz with attention to the scholarship of videogame protests in the northeast Asian context, this paper makes the case that Hong Kong's videogame activism inherits strategies and tactics that have appeared elsewhere in Taiwan and Mainland China.…”
Section: Introductionmentioning
confidence: 92%
“…Koenitz (2014) and Sezen and Sezen (2016) have each investigated how Turkey's protest games such as Occupy Istanbul (2013) appropriate game structures, logics, discourses, and popularity to showcase forms of civic participation within the safety of the virtual domain, but in ways that might draw players into the actual activist frontlines. Drawing on previous work by Emre et al (2014), Demirbag-Kaplan and Kaplan-Oz (2018) have suggested that a new grammar of playful resistance that is identifiable across both the Tahrir Square and Hong Kong protests is founded in a ubiquitous recognition and understanding of the game-like qualities of social and political unrest. Extending upon Demirbag-Kaplan and Kaplan-Oz with attention to the scholarship of videogame protests in the northeast Asian context, this paper makes the case that Hong Kong's videogame activism inherits strategies and tactics that have appeared elsewhere in Taiwan and Mainland China.…”
Section: Introductionmentioning
confidence: 92%